The effectiveness of food delivery service during movement control order in Malaysia / Muhamad Hanif Hashim - Hashim, Muhamad Hanif (2020)
This study is about the effectiveness of food delivery service during Movement Control Order in Malaysia. Throughout the duration of the Movement Control Order, any business activity including food service industry that involving face-to-face approach is not permitted unless the business involves food delivery services. Therefore, the objectives of this study are to identify the factors influencing food delivery service and to identify the impact of Movement Control Order towards food delivery service. Secondary data was used in this study which refers to previously gathered research data. The data was gathered from selective past internet, journals, blogs, books, online magazines, newspapers, and articles related to this research study. Findings show that time-saving, discount, delivery experience and restaurant close for dine-in are vital factors that caused the food delivery service being chosen. Besides that, the impact of Movement Control Order towards food delivery service is the demand for these services are increasing and causes more delivery riders to be employed. In addition, the spread of Covid-19 caused the contactless delivery service to be introduced.